KINERJA MANAJERIAL PEMERINTAH DESA ARGAPURA MELALUI PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN - Melia Wida Rahmayani; Engkun Kurnadi; Wulan Riyadi; Nita Hernita; Ayu Gumilang Lestari (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Managerial performance is very important for the survival of organizations, especiallygovernment organizations because it is the result of the organization's work in carrying outcommunity service activities. Efforts to improve managerial performance throughParticipation in Budgeting and Clarity of Budget Targets. The purpose of this study is todetermine the extent to which Participation in Budgeting and Clarity of Budget TargetsAffects the Managerial Performance of the Argapura Village Government. The method used isdescriptive verification in which the researcher describes the state of budgetary participation,clarity of budget targets and managerial performance of the village government of Argapura.The analysis used in this study uses partial hypothesis testing, multiple linear regressionanalysis, and analysis of the coefficient of determination. The results of this study have asignificant effect between variables